Minimum wage and real wage: Case Study for the Colombian coffee growing axis (2019)
The article studies the minimum wage policy in Colombia’s history in theinternational context and the rise inside the country, the legal and economicconsequences and its effects on both business dynamics and labor policy.Although the effects of national regulation and its impact in real terms isdifferent for every region in the country. The characteristics of each region andsocioeconomic conditions dictate that there are significant differentials in realincome received by employees in each of the cities. Therefore the behavior ofthe minimum wage in the Colombian coffee growing axis is studied.